2021
DOI: 10.3390/coatings11091023
|View full text |Cite
|
Sign up to set email alerts
|

Ca-Doped ZnO:Al Thin Films: Synthesis and Characterization

Abstract: We unveiled the effect of doping on the morpho-structural and opto/electrical properties of Ca-doped ZnO:Al thin films obtained by RF magnetron sputtering. Scanning electron microscopy (SEM) was performed to reveal the surface morphology, while the composition and crystal structure were investigated by energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD). The correlation between the microstructure and the electrical conductivity identifies an increase in electrical conductivity up to 145 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…As we noted above, co-doping is one of the most promising ways to solve the urgent problem of improving the microstructure of ZnO-based TCO films and, consequently, their electrical characteristics [ 11 , 12 , 13 , 14 , 15 , 37 ]. To be fully aware of the aspects leading to the improved crystallization and enhanced conductivity of the co-doped ZnO-based TCO films, the role of each introduced impurity has to be considered separately and in combination with each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we noted above, co-doping is one of the most promising ways to solve the urgent problem of improving the microstructure of ZnO-based TCO films and, consequently, their electrical characteristics [ 11 , 12 , 13 , 14 , 15 , 37 ]. To be fully aware of the aspects leading to the improved crystallization and enhanced conductivity of the co-doped ZnO-based TCO films, the role of each introduced impurity has to be considered separately and in combination with each other.…”
Section: Resultsmentioning
confidence: 99%
“…However, for the wider use of the ZnO-based TCO films as transparent electrodes in modern optoelectronic devices, some improvements in thin films’ performance regarding their electrical properties and long-term stability are further required both by optimizing the thin-film deposition processes and by tuning the film doping. Regarding the doping optimization, if a large number of earlier studies were devoted to finding the best donor for ZnO TCO films, as well as optimizing the level of doping, an increasing number of reports have recently appeared indicating that the simultaneous co-doping of ZnO with two or more types of impurities leads to a noticeable improvement in the electrical characteristics of TCO films, as well as their microstructures [ 10 , 11 , 12 , 13 , 14 , 15 ]. In particular, we have shown that the co-doping of ZnO with Ga and B leads to the formation of denser films with an improved film microstructure and, as a result, to an increase in the thermal stability of ZnO TCO films [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been reported by other authors, even when the Al,Ca-doped ZnO composites were prepared by different synthesis methods [ 12 ]. As an explanation of this, we may focus attention on the large difference in the atomic radius between zinc (1.42 Å) and calcium (1.94 Å), leading to lattice structure distortion, which consequently limits the growth of the wurtzite grains [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The advantages and disadvantages of these deposition techniques are highlighted as shown in Table 1. The prepared thin films could be used in lasers, cathodic ray tubes, solar cells [6], infrared windows, ultraviolet light-emitting diodes, sensors [7], supercapacitors, and biologic and optoelectronic applications [8].…”
Section: Introductionmentioning
confidence: 99%